THE INFLUENCE OF FOODVLOGGER @DEDEKARFANDA'S CONTENT ON TIKTOK ON CONSUMER BUYING INTEREST "BUKAN AYAM GEPREK BANG DEDEK" - Safira, Nabilla; Razzaq, Abdur; Nugraha, Muhamad Yudistira (Jurnal Buana Kata: Pendidikan, Bahasa, dan Ilmu Komunikasi, 2025)
The development of technology and social media has changed how social interaction and communication are handled, providing significant opportunities in business marketing. With more than 221 million internet users in Indonesia in 2024, social media, especially TikTok, has become an important platform for product and service promotion. This study aims to determine whether there is an influence of food vlogger content @dedekarfanda on TikTok on consumer purchasing interest, "not bang dedek's geprek chicken". The primary basis of this study uses the Uses and Effects Theory. This research method uses a quantitative approach with a survey method. This study aims to analyze the influence of food vlogger content @Dedekarfanda on TikTok on consumer purchasing interest. Using a quantitative approach, data was collected through a questionnaire distributed to 70 account followers. The analysis results show a significant linear relationship between the content produced by @Dedekarfanda and consumer purchasing interest, with a significance value of 0.00, which is smaller than 0.05. This finding confirms that marketing strategies through influencers on social media can effectively influence purchasing decisions and shows the great potential of TikTok as an efficient and affordable marketing tool. This research provides insight for business actors in utilizing social media to increase sales and build relationships with consumers.